2012
DOI: 10.1002/smll.201102464
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Encapsulation of Cells in Polymer Microgels

Abstract: In this Concept article, recent advances in microfluidic platforms for the generation of cell-laden hydrogel particles (microgels) are reported. Advances in the continuous microfluidic encapsulation of cells in droplets and microgels are critically reviewed, and currently used methods for the encapsulation of cells in polymer microgels are discussed. An outlook on current applications and future directions in this field of research are also presented. This article will be of interest to chemists, materials sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
241
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 69 publications
0
241
0
3
Order By: Relevance
“…This droplet-based method is rapid and high throughput. Velasco et al [123] demonstrated that cell-loaded hydrogel droplets significantly reduced the intensive labour needed to fabricate MCSs. In the porous micro droplets, oxygen and nutrients were diffused in and metabolic waste diffused out to maximize the cell viability [124].…”
Section: Micro-droplets-based Multicellular Spheroid Formationmentioning
confidence: 99%
“…This droplet-based method is rapid and high throughput. Velasco et al [123] demonstrated that cell-loaded hydrogel droplets significantly reduced the intensive labour needed to fabricate MCSs. In the porous micro droplets, oxygen and nutrients were diffused in and metabolic waste diffused out to maximize the cell viability [124].…”
Section: Micro-droplets-based Multicellular Spheroid Formationmentioning
confidence: 99%
“…The microfluidic technique generated microgels with a 6.22% polydispersity while vortexing produced particle samples with an average polydispersity of 23.62%, Monodispersity of microgels generated by microfluidics has been shown to be increased by further reducing channel and particle size 26 . Well-controlled size distributions holds enabling consequences for precision cell encapsulation 61 and high throughput cell screening 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinking PEG-4MAL macromers can be accomplished with dithiol molecules and does not require free radical initiators, which are detrimental to encapsulated cell health 13 . Similar microfluidic schemes for producing microgels [14][15][16] and encapsulating cells [17][18][19] have recently been reported for widely varying applications, including wound healing, stem cell culture and fundamental studies of cell biology. The versatility of microfluidic cell encapsulation extends to other polymers, including Matrigel 20 , agarose 21 and even multilayer core-shell composites such as collagen cores with alginate shells 22 .…”
Section: Introductionmentioning
confidence: 89%